Rancang Bangun Aplikasi Pencatatan Penjualan Berbasis Android dan MySQL - Ismail, Ibnu; Atmaja, Tri (Himpunan Dosen Gemilang Indonesia (HDGI), 2023)
At this time, the need for information is increasingly urgent and urgent in line with increasingly advanced technological developments. Many companies that want to be big or small use computers to support activities within their companies. Computers and their applications are currently not something new anymore, almost all large and small business entities have used computers as a means of supporting the activities of these companies. This study aims to create an Android-based sales recording application and use the MySQL database. System design using UML. Using this sales information system can simplify and speed up the performance of the sales department and can control the amount of inventory